Implemetasi ERP berbasis odoo untuk meningkatkan efektivitas point of sale dan accounting - Siti Lailatus Sak'adah (Department of Accounting Universitas PGRI Yogyakarta, 2024)
Micro, small, and medium enterprises (MSMEs) play a significant role in Indonesia's economic development. Many MSMEs still process financial transactions and prepare financial reports manually, thereby increasing the risk of errors. This study aims to assist in developing an accounting information system based on an Odoo-based ERP for Rumah Makan Gubug Mang Dikin. The research employs a qualitative method of describing data or facts by collecting data through observation, interviews, and document analysis. This approach aims to describe the actual conditions and identify system needs that can be addressed with an Odoo-based ERP. The study results indicate that implementing an Odoo-based ERP system provides significant benefits, particularly in point-of-sale and accounting, enhancing the operational effectiveness of MSMEs, accelerating administrative processes, and generating accurate, automated data. These data can serve as a reference for making precise decisions for MSMEs. This enables MSMEs to manage resources effectively and make more informed decisions, potentially improving performance and competitiveness.